SUSTAINABILITY REPORT DISCLOSURE: ALAT UNTUK MENIPU ATAU MEMBANGUN KEPERCAYAAN STAKEHOLDER - Siti Nurlatifah (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
This study aims to examine the effect of profitability, firm size, audit committee, and board of directors on sustainability report disclosure of mining sector companies listed on the Indonesia Stock Exchange (IDX). This study uses secondary data in the form of financial statements and sustainability reports of companies in 2019-2020. The sample of this study consists of 60 companies that are selected by purposive sampling method. The data analysis technique used is multiple linear regression using SPSS 25 program. The results of this study show that profitability and audit committee have a positive and significant effect on sustainability report disclosure, while firm size and board of directors have no effect on sustainability report disclosure.